2015
DOI: 10.1002/ana.24332
|View full text |Cite
|
Sign up to set email alerts
|

A large animal model of spinal muscular atrophy and correction of phenotype

Abstract: Objectives Spinal muscular atrophy (SMA) is caused by reduced levels of SMN which results in motoneuron loss. Therapeutic strategies to increase SMN levels including drug compounds, antisense oligonucleotides or scAAV9 gene therapy have proved effective in mice. We wished to determine whether reduction of SMN in postnatal motoneurons resulted in SMA in a large animal model, whether SMA could be corrected after development of muscle weakness and the response of clinically relevant biomarkers. Methods Using in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 59 publications
8
96
0
1
Order By: Relevance
“…However, none of those previous studies focused specifically on myelinating Schwann cells, because ubiquitous promoters were used. Widespread expression was reported in some cases after AAV injection from the spinal cord to the brain in both adults and neonates (26,33), and even after AAV9 injection in large animal models (27,34). This is the first demonstration, to our knowledge, of a successful intrathecal approach to treating peripheral neuropathy by delivering a myelin-related gene and achieving widespread Schwann cell-specific expression.…”
Section: Discussionmentioning
confidence: 74%
“…However, none of those previous studies focused specifically on myelinating Schwann cells, because ubiquitous promoters were used. Widespread expression was reported in some cases after AAV injection from the spinal cord to the brain in both adults and neonates (26,33), and even after AAV9 injection in large animal models (27,34). This is the first demonstration, to our knowledge, of a successful intrathecal approach to treating peripheral neuropathy by delivering a myelin-related gene and achieving widespread Schwann cell-specific expression.…”
Section: Discussionmentioning
confidence: 74%
“…[37][38][39] Early restoration of enzyme activity to both neural and skeletal muscle tissue is likely to have the greatest effect on physiological outcomes related to treatment strategies as our studies and those of others have demonstrated time-dependent arrests in functional decline after gene therapy. 11,74,75 Reliance upon liver-derived GAA to target neural tissues is dependent upon crosscorrection of neighboring cells through secretion and reuptake of GAA, yet the protein is too large to cross the blood-brain barrier and therefore does not address the neuropathology related to Pompe disease. 6,31 For these reasons, ERT or exclusively hepatic gene transfer would not address glycogen accumulation particularly in the motor neurons involved with ambulation or respiration as evidenced by patients continuing to be wheelchairand ventilator-dependent after long-term treatment of ERT.…”
Section: Discussionmentioning
confidence: 99%
“…[89]. Very recently, AAV9-SMN1 intrathecal delivery has also successfully corrected the phenotype of a pig SMA model [98]. All of these successful reports culminated in the first clinical trial approved for the test of AAV9 in neurodegenerative disorders (NCT02122952) (see Table 2).…”
Section: Preclinical Studies For Cns Using Aav9mentioning
confidence: 99%